Suitability analysis of Lampung Bay waters for grouper Epinephelus sp. farming activities - Yulianto, Herman; Hartoko, Agus; Anggoro, Sutrisno; Hasani, Qadar; Mulyasih, Dwi; Delis, Putu Cinthia (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT Grouper Epinephelus sp. farming activities in Lampung Bay is limited to an area of 77 hectares, while areas that are potential to be used for grouper farming are still very wide. Therefore, this study aimed to assess the suitability of Lampung Bay waters for grouper farming activities. The study was conducted in 20 stations with ecological preference considerations. The parameters observed were physicochemical (water depth, temperature, water transparency, the load of suspended solids, pH, dissolved oxygen, salinity, nitrate, and phosphate) and biological parameters (phytoplankton abundance and chlorophyll-a concentration). After the data were completely obtained, the data were processed into suitability matrix resulting in scores that will be grouped into four classes, namely S1 (highly suitable), S2 (moderately suitable), S3 (marginally suitable), N (not suitable). The geostatistical model was used to perform the earth’s surface mapping based on biotic and abiotic parameters that were analyzed. Based on the results of the analysis in this study, the conditions of Lampung Bay waters were suitable for grouper farming activities. Marine area that could be used for grouper farming was 33,847.12 hectares (S1: 15,712.6 ha, S2: 13,294.7 ha and S3: 4,209.82 ha) in the area around Puhawang Island, Kelagian Island, Maitem Island, Tegal Island to Hurun Bay. Keywords: Lampung Bay, grouper, suitability analysis, fish farming ABSTRAK Kegiatan budidaya ikan kerapu Epinephelus sp. di Teluk Lampung masih terbatas pada lahan seluas 77 hektar, sedangkan lahan yang berpotensi digunakan untuk budidaya ikan kerapu masih sangat luas. Oleh karena itu, penelitian ini bertujuan mengkaji kesesuaian perairan Teluk Lampung untuk kegiatan budidaya ikan kerapu. Penelitian dilakukan di 20 stasiun dengan pertimbangan ecological preference. Parameter yang diamati yaitu parameter fisika-kimia perairan (kedalaman, suhu, kecerahan, muatan padatan tersuspensi, pH, oksigen terlarut, salinitas, nitrat, dan fosfat) serta parameter biologi (kelimpahan fitoplankton dan konsentrasi klorofil-a). Setelah data parameter terpenuhi, data diolah ke dalam matriks kesesuaian sehingga menghasilkan skor yang akan dikelompokkan ke dalam empat kelas, yaitu S1 (highly suitable), S2 (moderately suitable), S3 (marginally suitable), N (not suitable). Model geostatistik digunakan untuk melakukan pemetaan permukaan bumi berdasarkan data parameter biotik dan abiotik yang dianalisis. Berdasarkan hasil analisis pada penelitian ini, kondisi perairan Teluk Lampung sesuai untuk kegiatan budidaya ikan kerapu. Luas perairan laut yang dapat digunakan untuk kegiatan budidya ikan kerapu yaitu, 33.847,12 hektar (S1: 15.712,6 ha, S2: 13.294,7 ha dan S3: 4.209,82 ha) di daerah sekitar Pulau Puhawang, Pulau Kelagian, Pulau Maitem, Pulau Tegal hingga Teluk Hurun. Kata kunci: Teluk Lampung, ikan kerapu, analisis kesesuaian, budidaya